A new kind of parameter conjugate gradient for unconstrained optimization - Basim Abbas Hassan; Hussein O. Dahawi; Azzam S. Younus (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper, a replacement new parameter conjugate gradient  for unconstrained optimization. The sufficient descent property cleave to. The global convergence property of the new method is proved under some assumptions. Numerical results explain that the  new parameter is superior  in practice.